Characterizing damage to a concrete liner during a tunnel fire. (March 2021) - Hua, Nan; Tessari, Anthony; Elhami Khorasani, Negar
Highlights: The spatial and temporal distributions of fire temperature within the tunnel is presented from a series of FDS simulations. A simplified method to incorporate concrete spalling in finite-element modeling is proposed. Fire damage to a tunnel liner is characterized using temperature criteria and structural response. Damaged volume of concrete, including spalling, is quantified for a range of fire scenarios. Stability of the tunnel structure is checked for extreme fire scenarios. Abstract: There are no available guidelines or methodologies to design the concrete lining in a tunnel for loss of functionality following a fire event. Historical tunnel fires confirm that tunnel downtime following an extreme event can lead to major economic losses, while fire protection design of the concrete lining can be adjusted to minimize losses. This paper provides a framework to characterize fire damage in a tunnel structure, where spatial and temporal distributions of fire temperature within a tunnel structure are modeled, and statistics of the potential damaged volume of the concrete lining that would require repair are quantified. A simplified spalling model, considering an initiation time, rate of spalling, and finishing time, is incorporated within the analysis to provide a more realistic measure of the damage. The results show that incorporation of spalling makes a significant difference in the damage assessment. Structural stability of the tunnel is checked under an extreme fire scenario to verify that, while experiencing extensive damage, the structure does not collapse. This paper focuses on a passenger railway tunnel, and is a first step in establishing a risk-based framework to guide fire protection design of a tunnel lining. The proposed approach can be applied to other tunnel types.